PENINGKATAN PENJUALAN PRODUK UMKM MELALUI PENDAMPINGAN PENGEMASAN PRODUK (PACKAGING) DI DESA BALESARI KECAMATAN WINDUSARI KABUPATEN MAGELANG - Andhatu Achsa; Dinar Melani Hutajulu; Fitrah Sari Islami (Universitas Muhammadiyah Tapanuli Selatan, 2022)
MSMEs product of Balesari Village, namely snacks, still have limitations in the product distribution area, in traditional markets. In addition, the level of product sales is also fluctuating due to the lack of consumer buying interest in the product. Consumers are less interested in the appearance of products that are still traditional, without brand labels and product permits. Furthermore, there has been no assistance on good product packaging to increase the selling value of the product. The purpose of this service activity is to provide assistance to MSMEs related to product packaging, mentoring and training on product design making, as well as discussions regarding attractive product brands. This service activity uses 3 methods in its implementation, the first method is the lecture and mentoring method, the second is the tutorial method and the third is the discussion method. From the implementation of these activities, about 85% of the assisted communities, namely entrepreneurs, have understood the importance of good and safe packaging and can make packaging that is suitable for the type of MSMEs products. About 90% of entrepreneurs understand the importance of product design and how to make a product design that fits the market segment of the product. Approximately 95% of MSMEs entrepreneurs have determined their product brands based on the results of discussions conducted with the service team.